Preterm labour and its effect on perinatal morbidity and mortality - Gupta, Neetu; Divedi, Pragati; Dwivedi, Deepti (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: This study was performed to find out the incidence and identification of risk factors of preterm labour and also to find out the incidence of perinatal outcome in the form of morbidity and mortality. Methods: Total 720 antenatal cases with preterm labour admitted and studied in total one-year duration in UPUMS Saifai, Etawah. Out of 720 cases, 692 pregnant patients underwent preterm birth. Thorough history taking, general, systemic and obstetrical examination was done for each patient. APGAR Score and birth weights of the new borns were noted at the time of birth and they were followed up throughout the hospital stay. Incidence and perinatal morbidity and mortality of preterm births were calculated. Results: Incidence of preterm labour and births were 28.5% and 27.9% respectively. Among various causes of pre-term birth, spontaneous labour with intact membranes is the most common cause. Lack of antenatal check-up was found to be most common risk factor of preterm labour followed by infection and low socioeconomic status. Majority of the new-borns had low APGAR score (<6) in the present study. Total perinatal morbidity in the present study group was 67.2% Conclusions: We concluded that higher incidence of perinatal morbidity and mortality may be due to that the study was conducted at tertiary health care hospital which mostly receive high risk cases and majority of cases belonged to low socioeconomic group and also that the incidence of perinatal morbidity and mortality may be more in this part of country.